Developing a Model of Islamic Banking Audit Understanding Based on Student Learning Experiences: A Grounded Theory Approach - Wali Saputra (Indo Publishing, 2025)
This study aims to develop a model of Islamic banking audit understanding based on students’ learning experiences using a Grounded Theory approach. Islamic banking audit carries unique complexities because it must consider sharia compliance alongside conventional accounting and auditing practices. The study involved 25 accounting students who had completed coursework in auditing and Islamic banking at three universities in Indonesia. Data were collected through semi-structured in-depth interviews and focus group discussions (FGDs), and analyzed using open, axial, and selective coding following Strauss and Corbin’s Grounded Theory procedures. The findings identify five key categories in students’ understanding of Islamic banking audit: (1) foundational understanding of sharia principles, (2) technical auditing competencies, (3) integration of sharia–accounting knowledge, (4) learning challenges, and (5) strategies for developing understanding. The resulting theoretical model shows that students’ understanding develops through an iterative process influenced by their religious knowledge background, instructional quality, and practical exposure. This model offers important implications for curriculum design and instructional methods in Islamic banking audit education at the higher education level.